Innovative Pedagogical Approaches to Teaching Landscape Art in Secondary School Visual Arts Classes - Nurimova Shaxlo Shuhratovna (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2026)
This article explores innovative pedagogical approaches for teaching landscape painting in secondary school visual arts classes. It examines methods for developing students’ observation skills, compositional thinking, color perception, and creative abilities. The study highlights the effectiveness of plein-air activities, digital tools, group projects, and reflective practices in fostering independent artistic expression. Recommendations are provided for structuring lessons that enhance students’ aesthetic literacy, creative thinking, and engagement with the landscape genre.